Exploration of perceived effects of innovations in postgraduate medical education. Issue 3 (8th February 2013) - Fokkema, Joanne P I; Teunissen, Pim W; Westerman, Michiel; van der Lee, Nadine; van der Vleuten, Cees P M; Scherpbier, Albert J J A; Dörr, P Joep; Scheele, Fedde
<x xml:space="preserve">Abstract</x> Context Many studies have examined how educational innovations in postgraduate medical education (PGME) impact on teaching and learning, but little is known about effects in the clinical workplace outside the strictly education‐related domain. Insights into the full scope of effects may facilitate the implementation and acceptance of innovations because expectations can be made more realistic, and difficulties and pitfalls anticipated. Using workplace‐based assessment (WBA) as a reference case, this study aimed to determine which types of effect are perceived by users of innovations in PGME. Methods Focusing on WBA as a recent instance of innovation in PGME, we conducted semi‐structured interviews to explore perceptions of the effects of WBA in a purposive sample of Dutch trainees and (lead) consultants in surgical and non‐surgical specialties. Interviews conducted in 2011 with 17 participants were analysed thematically using template analysis. To support the exploration of effects outside the domain of education, the study design was informed by theory on the diffusion of innovations. Results Six domains of effects of WBA were identified: sentiments (affinity with the innovation and emotions); dealing with the innovation; specialty training; teaching and learning; workload and tasks, and patient care. Users' affinity with WBA partly determined its effects on teaching and learning. Organisational support and the match between the innovation and routine practice were considered important to minimise additional workload and ensure that WBA was used for relevant rather than easily assessable training activities. Dealing with WBA stimulated attention for specialty training and placed specialty training on the agenda of clinical departments. Conclusions These outcomes are in line with theoretical notions regarding innovations in general and may be helpful in the implementation of other innovations in PGME. Given the substantial effects of innovations outside the strictly education‐related domain, individuals designing and implementing innovations should consider all potential effects, including those identified in this study.